Adipose micro‐grafts enhance tendinopathy healing in ovine model: An in vivo experimental perspective study. (16th August 2021) - Palumbo Piccionello, Angela; Riccio, Valentina; Senesi, Letizia; Volta, Antonella; Pennasilico, Luca; Botto, Riccardo; Rossi, Giacomo; Tambella, Adolfo Maria; Galosi, Livio; Marini, Carlotta; Vullo, Cecilia; Gigante, Antonio; et al.
Abstract: In Europe, approximatively 100 000 to 500 000 tendon repairs are performed every year. These procedures are associated with a considerable rate of postoperative complications (from 6% to 11%). Autologous micro‐grafts (AAMG) and stromal vascular fraction (SVF) have been shown to improve tendon healing in 60% to 70% of treated rodents. The purpose of this study was to evaluate the effects of AAMG in a sheep model with tendinopathy. We used sheep models because, as a large animal, they are more comparable to humans. The hypothesis was that SVF injection would improve tendon healing compared with the control group, reducing inflammatory and matrix degrading, while increasing anti‐inflammatory expression and collagen synthesis in the early stage of tendon injury. Sixteen Apennine sheep aged 2 to 5 years underwent 500 UI type I collagenase injection into both common calcaneal tendons (CCT) to induce tendinopathy. After 15 days (T0), one CCT in every ovine underwent randomly to 2.5 mL of AAMG obtained by mechanical disruption and the contralateral CCTs received no treatment. Clinical, ecographic, and sonographic evaluations were performed after 4 weeks (T1) and 8 weeks (T2). Histological, immunohistochemical, real‐time polymerase chain reaction (RT‐PCR), and biomechanical evaluations were performed at T2. At T2, the treated group showed a final tendon diameter (9.1 ± 1.4 mm) and a hardness expression (62%) that were similar to the original healthy tendon (8.1 ± 1.1 mm; 100%), with a significant recovery compared with the control group (9.5 ± 1.7 mm; 39%). Moreover, histological analysis of the treated group revealed an improvement in the fiber orientation score, fiber edema score, infiltrative‐inflammatory process, and necrosis score (4.3 ± 3.3) compared with control group (8.8 ± 2.9). Immunohistochemically, the treated group showed high expression of collagen 1, Factor VIII and significantly low expression of collagen 3. These data were confirmed by RT‐PCR analysis. The study findings suggested that AAMGs obtained through mechanical disruption present a safe, efficient, and reliable technique, enhancing tendon healing. Abstract : The group treated with stromal vascular fraction showed a final tendon diameter and a percentage hardness expression that were similar to the original healthy tendon.